2006
DOI: 10.1158/0008-5472.can-06-2526
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Oncogenic Transcription and Alternative Splicing by β-Catenin and an RNA Aptamer in Colon Cancer Cells

Abstract: Activated B-catenin regulates the transcription of oncogenic target genes and is critical for tumorigenesis. Because nuclear functions are frequently coupled, we investigated whether it also has a role in alternative splicing of oncogenic genes. We showed that stabilized B-catenin caused alternative splicing of estrogen receptor-B pre-mRNA in colon cancer cells. To establish a direct role of B-catenin in regulated splicing, we selected a high-affinity RNA aptamer that associated with B-catenin in vivo . Nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 39 publications
1
58
0
2
Order By: Relevance
“…Furthermore, ␤-catenin has been recently reported to influence pre-mRNA splicing (Sato et al, 2005;Lee et al, 2006), a process where PNN is also involved (Li et al, 2003;Zimowska et al, 2003). Even though the relevance of these functional commonalities needs further investigation, our in vivo studies may provide a crucial insight into PNN's connection to a signaling pathway, which may govern biological processes in which PNN has been shown to be involved.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, ␤-catenin has been recently reported to influence pre-mRNA splicing (Sato et al, 2005;Lee et al, 2006), a process where PNN is also involved (Li et al, 2003;Zimowska et al, 2003). Even though the relevance of these functional commonalities needs further investigation, our in vivo studies may provide a crucial insight into PNN's connection to a signaling pathway, which may govern biological processes in which PNN has been shown to be involved.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, recent studies suggested that the oncogenic activity of ␤-catenin may include its ability to influence premRNA splicing, thus allowing the production of cancer-associated splicing variants (Sato et al, 2005;Lee et al, 2006;Shitashige et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, overexpression and unregulated expression of β-catenin regulates RNA alternative splicing and RNA stabilization in colon cancer cells (48)(49)(50). Overexpressed β-catenin upregulates cyclinD1 and c-myc mRNA transcription as transcription factors in cancer cells.…”
Section: Rbps Implicated In Cancermentioning
confidence: 99%
“…RNA aptamers are short RNA oligonucleotides forming a stable three-dimensional structure for specific tight binding to target protein (64)(65)(66)(67). RNA aptamers binding to target proteins are selected from combinatorial libraries by using SELEX method.…”
Section: Other Therapeutics Targeted To Fgfr2mentioning
confidence: 99%